The Epistle of the eloquent clarification concerning the refutation of Ibn Qutayba - Nuʻmān ibn Muḥammad, Abū Ḥanīfah, d. 974. (Islamic History and Civilization, 2012)
This is an edition of an early Shiite/Fatimid Arabic epistle that includes a controversy pertaining to several issues on Islamic law. Al-Qadi al-Nu'man (d. 363/974), the most famoust jurist of the early Fatimid period refutes the illustious Ibn Qutayba (d. 276/889). In his book Adab al-Katib, Ibn Qutayba claimed that it was enough for civil servants (kuttab) to memorize a few legal formulas in order to be able to effectively do their work without the need of long dissertations on law from jurists. In the introduction to his epistle, al-Nu'man claims that without these dissertations the civil servants would not be able to apply the law correctly. Following this, al-Nu'man launches lengthy dissertations on each one of the succinct formulas listed by Ibn Qutayba. The main argument of al-Nu'man is that the only lawgivers in Islam are the prophet Muhammad and the Imams descendents of Ali (until the seventh Imam).